2016
DOI: 10.1103/physrevd.93.084015
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and exact critical phenomena ofd-dimensional singly spinning Kerr-AdS black holes

Abstract: In the extended phase space, the d-dimensional singly spinning Kerr-anti-de Sitter black holes exhibit the van der Waals phase transition and reentrant phase transition. Since the black hole system is a single-characteristic-parameter system, we show that the form of the critical point can be uniquely determined by the dimensional analysis. When d = 4, we get the analytical critical point. The coexistence curve and phase diagram are obtained. The result shows that the fitting form of the coexistence curve in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 71 publications
(88 reference statements)
1
56
0
Order By: Relevance
“…9(b), two metastable phases, the superheated small black hole and supercooled large black hole, are clearly shown. A detailed study of the superheated small black hole and supercooled large black hole can be found in [66].…”
Section: Thermodynamics and Phase Structuresmentioning
confidence: 99%
“…9(b), two metastable phases, the superheated small black hole and supercooled large black hole, are clearly shown. A detailed study of the superheated small black hole and supercooled large black hole can be found in [66].…”
Section: Thermodynamics and Phase Structuresmentioning
confidence: 99%
“…It is quite clear that the reduced state equation (24) is independent of the parameter α, which is mainly because that the neutral GB-AdS black hole is a single-characteristic-parameter system [41]. Moreover, we can express the state function with the thermodynamic volume…”
Section: Thermodynamics and Phase Transitionmentioning
confidence: 99%
“…This traditional method has been extensively applied to the characterization of general thermodynamic systems and also to the establishing of complete simulation for AdS spacetime black hole thermodynamic liquid/gas system [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%